2021
DOI: 10.1186/s12886-021-02071-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myopia in 3–14-year-old Chinese children: a school-based cross-sectional study in Chengdu

Abstract: Background The prevalence of myopia among children in Chengdu is unknown. The aim of this study was to determine the prevalence of myopia in 3- to 14-year-old Chinese children in Chengdu. Methods This study was a school-based cross-sectional study in children aged 3–14 years. Visual acuity (VA), spherical equivalent error (SER) with noncycloplegic autorefraction, axial length (AL) and corneal radius (CR) were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
13
2
Order By: Relevance
“…There were 532,851 boys, accounting for 50.28% of the study participants. The mean age was 11.57 ± 3.36 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 532,851 boys, accounting for 50.28% of the study participants. The mean age was 11.57 ± 3.36 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) years.…”
Section: Resultsmentioning
confidence: 99%
“…Another school-based cross-sectional study enrolled 3–14-year-old Chinese children in Chengdu by Wang et al demonstrated that the prevalence of low myopia in the girls was higher than that in the boys (28.4 vs. 25.0%), while the prevalence of moderate myopia (9.5 vs. 10.1%), and high myopia (SE ≤ −6.00 D, 1.7 vs. 1.7%) did not significantly differ between the girls and boys ( 15 ). In our study, the total prevalence of myopia in the girls was higher than that in the boys, which is consistent with those in previous studies ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the effect of strong accommodation, myopia was additionally assessed by both non-cycloplegic autorefraction and visual acuity in our study. In the report by Wang et al, which assessed myopia in a similar manner, myopia was prevalent in 2.6% and 1.7% of children aged 4 and 5 years, respectively ( 18 ). Relatively close values were obtained in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the criteria for younger children aged 3–6 years should be determined carefully for each age group because the average visual acuity varies with age ( 16 ). Hence, following the previous method, myopia was defined as SE ≤ – 0.50 D + uncorrected visual acuity > 0.3 logMAR for children aged 3 years, > 0.2 logMAR for children aged 4–5 years, and > 0 logMAR for children aged 6 years ( 18 ). Analysis was performed on the worse eye only in view of the correlation in parental myopia, outdoor time and near work between right and left eyes ( 2 , 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation